The Influence Of A Miscellaneous Approach To Improving Science Learning Outcomes Of Class Iv Students Of Madrasah Ibtidaiyah Amanah Kandis City - Irasari, Irasari; Sulistia, Ade (Journal of Sustainable Education, 2024)
The aim of this research is to influence the thinking approach on the science learning outcomes of grade IV students at Mi Amanah Kandis Kota and the influence of the thinking approach on the science learning outcomes of grade IV students at Mi Amanah Kandis Kota. This research method is quantitative research with a Quasi Experimental Design approach, collecting data using research instruments, systematic quantitative data analysis, with the aim of testing predetermined hypotheses. The results of this research indicate that the MIKIR approach has a significant positive influence on students' interest in learning in science subjects. Students who are involved in learning with the MIKIR approach show a higher level of interest compared to students who take part in conventional learning. This approach encourages students to be active in the learning process, increases creativity, and strengthens social interactions between students. Apart from that, the research results also show that using the MIKIR approach can improve students' understanding of concepts and application of knowledge. Students tend to better understand science subject matter and are able to relate it to real world situations through inquiry and reflection-based learning.